Implementasi Manajemen Kelas dalam Meningkatkan Keefektifan Pembelajaran Tafsir Ahkam di MTs al Urwatul Wutsqo Jombang - Mar'atul Azizah (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2017)
This study describes the implementation classroom management in increasing the learning effectiveness of Tafsir Ahkam at MTs Al Urwatul Wutsqo Bulurejo Diwek Jombang. This study uses qualitative approach in the form of case study. The data collection in this study used participant observation, in depth interview, and documentation. To test the validity of data, the researcher used extension study, perseverance observation, and triangulation. The results are 1) the lesson plan of Tafsir Ahkam at MTs Al Urwatul Wutsqo Jombang included creating syllabus, lesson plan, semester and the annual program. 2) The organizing classes started from grouping students based on their intelligence, organizing students discipline to keep classroom conducive, organizing methods and means to further emphasize the forms of learning that will be conducted. 3) The implementation of Tafsir Ahkam teacher is the teacher mastery of material, classroom condition, and the learning approach. 4) classroom evaluation is conducted by assessing of each meeting both cognitive and affective. However, the students affective is an important consideration in determining the score obtained the students.